The ballad collectors of North America : how gathering folksongs transformed academic thought and American identity - Spencer, Scott B., 1970- (American folk music and musicians, 2012)
Both biographical and topical, The Ballad Collectors of North America chronicles those individuals most influential in the gathering of North American folksongs and investigates the two leading schools of thought regarding the collection process, the le.